A review of solar photovoltaic systems cooling technologies - Siecker, J.; Kusakana, K.; Numbi, B.P. (Renewable and Sustainable Energy Reviews, 2017)
Cooling the operating surface is a key operational factor to take into consideration to achieve higher efficiency when operating solar photovoltaic systems. Proper cooling can improve the electrical efficiency, and decrease the rate of cell degradation with time, resulting in maximisation of the life span of photovoltaic modules. The excessive heat removed by the cooling system can be used in domestic, commercial or industrial applications. This paper presents a review of various methods that can be used to minimize the negative impacts of the increased temperature while making an attempt to enhance the efficiency of photovoltaic solar panels operating beyond the recommended temperature of the Standard Test Conditions (STC). Different cooling technologies are reviewed, namely Floating tracking concentrating cooling system (FTCC); Hybrid solar Photovoltaic/ Thermal system cooled by water spraying; Hybrid solar Photovoltaic/ Thermoelectric PV/TE system cooled by heat sink; Hybrid solar Photovoltaic/Thermal (PV/T) cooled by forced water circulation; Improving the performance of solar panels through the use of phase-change materials; Solar panel with water immersion cooling technique; Solar PV panel cooled by transparent coating (photonic crystal cooling); Hybrid solar Photovoltaic/Thermal system cooled by forced air circulation, and Solar panel with Thermoelectric cooling. Several research papers are reviewed and classified based on their focus, contribution and the type of technology used to achieve the cooling of photovoltaic panels. The discussion of the results has been done based on the advantages, disadvantages, area of application as well as techno-economic character of each technology reviewed. The purpose of this review is to provide an understanding for each of the above-mentioned technologies to reduce the surface temperature of the PV module. The study will focus on the surface temperature reduction array bound by each of the cooling technologies. The performance of each cooling technology will also be highlighted. In addition to this study, this review will include a discussion comparing the performance of each cooling technology. The outcomes of this study are detailed in the conclusion section. This paper has revealed that any adequate technology selected to cool photovoltaic panels should be used to keep the operating surface temperature low and stable, be simple and reliable and, if possible, enable the use of extracted thermal heat to enhance the overall conversion efficiency. The presented detailed review can be used by engineers working on theory, design and/or application of photovoltaic systems.
Published Article
Keywords: Solar photovoltaics; Cooling technologies; Efficiency; Literature review